Unveiling structure–property relationships of Fe-promoted Rh-Mn/UiO-66-drived catalysts for C2 oxygenates formation from syngas. (1st July 2022) - Chen, Guoqing; Xue, Xiaoya; Guo, Qiangsheng; Mao, Dongsen; Yu, Jun
Graphical abstract: The effect of iron promoter on the catalytic properties of Rh-Mn/UiO-66-drived catalyst was investigated by syngas conversion. The appropriate addition of Fe can enhance the Rh-Fe interaction, resulting in the enhancement of CO dissociation ability and strength of the Rh-CO bond, which should be responsible for the higher CO conversion and selectivity of C2 + oxygenates. Highlights: Fe-promoted Rh-Mn/UiO-66-drived catalysts were investigated by syngas conversion. The Rh-Fe interaction can promote the reduction of Rh active sites. The Rh 0 -rich state can enhance CO dissociation ability and Rh-CO bond strength. Abstract: The effect of iron promoter on the catalytic performance of Rh-Mn/UiO-66-drived catalyst was studied by syngas conversion. The catalysts were completely characterized by means of X-ray diffraction (XRD), N2 sorption, transmission electron microscopy (TEM), X-ray photoelectron spectra (XPS), diffuse reflectance infrared Fourier transform spectra (DRIFTS), and temperature-programmed surface reaction (TPSR). When the amount of Fe doping reached 0.3 wt%, the catalyst has the excellent catalytic activity with the highest C2 + oxygenates yield of 300.1 g/(kg·h). The results indicated that the appropriate addition of iron can enhance the Rh-Fe interaction, which promote the reduction of Rh active sites. The Rh 0 -rich state would be observed on the catalysts doped by the appropriate amount of Fe, resulting in the enhancement of CO dissociation ability and strength of the Rh-CO bond, which should be responsible for the higher conversion rate and selectivity of C2 + oxygenates.